THE EFFECT OF ENGLISH SHORT STORY READING HABIT ON STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT - Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2015)
This study investigates students' ability in writing narrative text, especially in terms of content, organization, vocabulary, language-used, and mechanic. The research was conducted at SMA N 9 Bandar Lampung. The sample was chosen by using systematic probability sampling. The study employed control group pretest posttest design. To collect the data, the writing test applied that was administered both in pretest and posttest. T-test was conducted to examine the difference between writing ability of both groups on writing test.  The mean score of the pretest for experimental class was 69.83 and for the control class was 68.55. Its two tailed significance showed that p>0.05 (p=.73), it indicates that the  writing ability of both classes was homogenous. At the end of the research, after fifteen meetings, the mean score of the posttest for experimental class was 75.05 and the control class was 65.61. Therefore, it is concluded that the students’ English Short Story Reading Habit has positive effect on students’ ability in writing narrative text. The findings also suggest that the English Short Story Reading Habit activities can be promoted as one of ways to fulfill the demands of 2006 curriculum in developing students’ ability in writing narrative text, the teacher just asks the students to have real experience by motivating them to read many kinds of English Short Stories in order to make them be able to gather their ideas in writing narrative text. Further research is required to replicate these findings.